The role of local government in the effective implementation of the National Environmental Management: Integrated Coastal Management Act 2008- a case of the Draft Cape Town Metropolitan Coastal Protection Zone Management by-Law - Lemine, Bramley Jemain (University of the Western Cape, 2015)
Magister Legum - LLM === The purpose of the study is to outline the relevant legislation and assess whether it is adequately applied to protect the 240 km coastline with its associated sensitive ecosystems; in particular, as assessment will be made of the By-law.